2019
DOI: 10.1101/547836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The number of lateral hypothalamus orexin/hypocretin neurons contributes to individual differences in cocaine demand

Abstract: Lateral hypothalamus (LH) orexin neuron signaling has been implicated in the motivation to seek and take drugs of abuse. The number of LH orexin neurons has been shown to vary with behavioral state and can be upregulated with exposure to drugs of abuse. We sought to determine if the number of LH orexin neurons related to individual differences in motivation (demand) for cocaine in our behavioral economics (BE) paradigm, and whether knockdown of these cells predicted changes in economic demand. We quantified LH… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The variable α has been shown repeatedly to correlate with drug-seeking for multiple drugs of abuse [61] and is associated with the propensity to develop a more severe SUD phenotype in cocaine self-administering rats [102]. Consistent with several previous studies indicating a functional dichotomy for LH versus DMH/PF orexin cells in reward and stress processes, respectively [60,64,103,104], we found that the number of LH (but not DMH/PF) orexin cells negatively correlated with heroin α. Interestingly, we observed no relationship between orexin cell numbers in either LH or DMH/PF and food α, indicating an apparent specific relationship between the LH orexin system in motivation for heroin. Moreover, positive correlations were observed between LH (but not DMH/PF) orexin cell numbers and heroin P max .…”
Section: Discussionsupporting
confidence: 88%
“…The variable α has been shown repeatedly to correlate with drug-seeking for multiple drugs of abuse [61] and is associated with the propensity to develop a more severe SUD phenotype in cocaine self-administering rats [102]. Consistent with several previous studies indicating a functional dichotomy for LH versus DMH/PF orexin cells in reward and stress processes, respectively [60,64,103,104], we found that the number of LH (but not DMH/PF) orexin cells negatively correlated with heroin α. Interestingly, we observed no relationship between orexin cell numbers in either LH or DMH/PF and food α, indicating an apparent specific relationship between the LH orexin system in motivation for heroin. Moreover, positive correlations were observed between LH (but not DMH/PF) orexin cell numbers and heroin P max .…”
Section: Discussionsupporting
confidence: 88%
“…This could be done through targeted microinjections of an antisense morpholino into the NacC and vmCP followed by analysis of alcohol preference and consumption or by measuring the neuronal activity of these ectopic neurons after behaviour to determine if they are participating in local neural circuitry. 59 Although both clinical and animal studies have shown embryonic ethanol exposure to produce ectopic neurons in the brain, 21,22,62 this report provides new evidence in both rats and zebrafish for ectopic neurons that express specific peptides known to promote alcoholrelated behaviours. It also characterizes the morphology of these neurons, showing them to be mature neurons but different from normally located neurons, and it presents in zebrafish the first direct evidence that these ectopic neurons are functional and involved in mediating ethanol-induced disturbances in behaviour.…”
Section: Discussionmentioning
confidence: 77%
“…This difference is likely due to the fact that embryonic peptide neurons when differentiating from neural progenitor cells are more susceptible than mature neurons to drug‐induced disturbances. It is notable that these other substances administered at older ages, such as fentanyl 57 and cocaine, 59 stimulate the density of Hcrt neurons similar to the effects of embryonic ethanol exposure and animals with more motivation for these substances have a greater number of Hcrt neurons. This suggests that there are common underlying mechanisms mediating these drug effects on this neuropeptide neuronal population, which in turn drives behaviours related to substance use disorders.…”
Section: Discussionmentioning
confidence: 99%
“…First, Ox1R signaling has been implicated in several psychiatric disorders that are commonly associated with deficient impulse control. Most notably, addiction is associated with higher numbers, activity and excitability of orexin cells (James et al, 2018b;Lawrence et al, 2006;Moorman et al, 2016;Pantazis et al, 2019;Thannickal et al, 2018;Yeoh et al, 2012Yeoh et al, , 2018, and SB is highly effective at reducing several addiction-related behaviors in rodents (Brodnik et al, 2018;Campbell et al, 2018;James et al, 2017James et al, , 2018aMartin-Fardon and Weiss, 2014a,b;Moorman et al, 2017;Perrey and Zhang, 2018;Schmeichel et al, 2017). Secondly, orexin neurons are interconnected with a variety of brain regions (e.g.…”
Section: Orexin Signaling and Inhibitory Controlmentioning
confidence: 99%